Cardiac Safety Research Consortium (CSRC): Cardiovascular Safety and Adverse Event Case Report Forms. (July 2015) - Sabol, Mary Elizabeth; Finkle, John; Krucoff, Mitch; Stockbridge, Norman; Parkhill, Nancy; Shinagawa, Kaori; Mahaffey, Kenneth; Tcheng, James; Lenihan, Daniel; Melloni, Chiara; Todaro, Thomas; Michelson, Eric; et al.
Detection of off-target cardiovascular (CV) effects remains a significant challenge to drug development. Documentation of CV events in non-CV trials is often inadequate to interpret imbalances between treatment arms, which may lead to concerns about potential CV safety "signals." The Cardiac Safety Research Consortium (CSRC) public-private partnership has developed CV case report forms (CRFs) for adverse CV events, including death. These CRFs are intended to encourage collection, as near to the occurrence of an event as possible, of the minimum information necessary to assess, or possibly adjudicate, the event. A broad range of stakeholders (representing industry, academia, and regulatory authorities) developed these forms with the goal of balancing the collection of key information with the resources likely to be available. Use of these forms is optional, and sponsors may modify them. These forms have not undergone any type of "validation" process. The CSRC will continue to sponsor a working group to invite public comment and feedback on these forms.